e-Kabisig App: Mobile Application Bayanihan Community Donation App with Geo-mapping - Del Prado, Kian M.; Mendiola, Neil Harvey D.; Balahadia, Francis Fernandez (International Journal of Computing Sciences Research, 2023)
Purpose- This study focuses on the development of a mobile application designed to facilitate donations of usable items such as clothes, food, and other goods to assist those in need within the community. The application features various tools, including a donation posting function, location mapping, and donor recognition points. Method- The study was conducted in small local government unit in Laguna and employed a combination of descriptive and developmental approaches utilizing the SDLC Waterfall Model for system development. Results- The study's results demonstrate that the mobile donation application is an effective tool to aid the community in donating easily while reducing waste and assisting those in need. The developed system gained highest rating of excellent for software evaluation both from system users/respondent s and IT experts. Conclusion- Ultimately, this study illustrates that the integration of mobile technology into the donation process can serve as a powerful tool for community support and waste reduction curbing the wastage of valuable resources and providing assistance to those in need. Recommendations- expanding the mapping coverage to encompass multiple municipalities and also implement the donations to encompass disaster and calamity scenarios, such as typhoons, fires, and earthquakes that can use to utilized as an emergency resource for municipalities. Research Implications – The developed system has the potential to help the community that effect on technology on giving the local government to reaching those in need. The study also integrate gamification that support user engagement and improve level of participation in the community and use the system as channel of donation and tool when emergency occurs.